2018
DOI: 10.3389/fpls.2018.01866
|View full text |Cite
|
Sign up to set email alerts
|

Jasmonate Zim-Domain Protein 9 Interacts With Slender Rice 1 to Mediate the Antagonistic Interaction Between Jasmonic and Gibberellic Acid Signals in Rice

Abstract: The jasmonic acid (JA) and gibberellic acid (GA) signaling pathways interact to coordinate stress responses and developmental processes. This coordination affects plant growth and yield, and is mediated by interactions between the repressors of each pathway, the JASMONATE ZIM-DOMAIN PROTEIN (JAZ) and DELLA proteins. In this study we attempted to identify rice (Oryza sativa) JAZs that interact with rice DELLAs such as SLENDER RICE 1 (SLR1). Analysis of protein–protein interactions showed that OsJAZ8 and OsJAZ9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 56 publications
2
21
0
Order By: Relevance
“…For example, JA interacts with gibberellic acid in the coordination of plant development and stress responses. [18][19][20] Based on our results presented here, we propose that JA interacts with auxin and CK to modulate xylem development. Further molecular and genetic studies will enhance our understanding of the molecular mechanisms underlying JA-mediated xylem development and the regulatory interactions between JA and other key phytohormones.…”
Section: Textmentioning
confidence: 54%
“…For example, JA interacts with gibberellic acid in the coordination of plant development and stress responses. [18][19][20] Based on our results presented here, we propose that JA interacts with auxin and CK to modulate xylem development. Further molecular and genetic studies will enhance our understanding of the molecular mechanisms underlying JA-mediated xylem development and the regulatory interactions between JA and other key phytohormones.…”
Section: Textmentioning
confidence: 54%
“…By triggering the degradation of DELLAs, GA suppresses ABI5-mediated ABA signaling via stabilized ICE1. Most interestingly, DELLAs [ 131 , 133 ], ICE1 [ 96 ] and ABI5 [ 160 , 161 ] are all targets of JAZ proteins ( Figure 7 ). Therefore, ABI5 appears to be the convergence point where ABA signaling is fine-tuned through the interaction of regulators coming from multiple signaling pathways (such as JA and cold).…”
Section: Crosstalk Complexity Of Ja With Other Phytohormonesmentioning
confidence: 99%
“…These studies suggested that the cytokinin response is integral to the JA-dependent stress response and growth modulation. A recent study using overexpression plants and knock-out mutants of OsJAZ9 revealed that OsJAZ9 is a key JAZ protein that mediates the antagonistic interaction of JA and GA [21]. In this study, they identified OsJAZ9 proteins that directly interact with the rice DELLA protein SLENDER RICE 1 (SLR1), and demonstrated that the OsJAZ9-SLR1 interaction mediates the antagonistic interaction of JA and GA in rice by showing that overexpression of OsJAZ9 promotes the GA response while knock-out of OsJAZ9 reduces the GA response.…”
Section: Cytokinin Metabolism and Signalingmentioning
confidence: 99%
“…However, the nature of the interaction appears to differ depending on the type of cell and tissue. For example, JA and GA antagonistically interact in stem elongation, while they interact synergistically in stamen development [21,104]. JA antagonistically interacts with auxin to modulate apical growth of roots, but synergistically to promote lateral root growth [93,105].…”
Section: Complexity Of Ja Crosstalkmentioning
confidence: 99%